The role of active soil carbon in influencing the profitability of fertilizer use: Empirical evidence from smallholder maize plots in Tanzania - Chamberlin, Jordan; Jayne, Thomas S.; Snapp, Sieglinde (Wiley, 2021)
We use recent plot-level panel data from Tanzanian smallholder farmers to investigate maize yield responses to inorganic fertilizer under variable soil carbon conditions. Unlike many prior studies which consider total carbon measurements, we focus on active soil carbon, which is a component strongly related to key soil functions, such as nutrient cycling and availability. Active soil carbon is found to be a strong predictor of maize yield response to nitrogen fertilizer. These results highlight important sources of variation in the returns to fertilizer investments across plots and smallholder farmers in the region. When farmgate prices for maize and fertilizer are incorporated into calculations of economic returns, we find that the profitability of fertilizer use is strongly dependent upon farmgate price ratio assumptions: under our most optimistic agronomic response estimates, 39% of farmer plots have an average value-cost ratio greater than 1.5 at a maize-nitrogen price ratio of 0.15. That share drops to 4% at a price ratio of 0.12 and 0% at a price ratio of 0.09. Our findings provide insights into the intertwined biophysical and economic underpinnings of low levels of fertilizer use in Tanzania and elsewhere in the region. Raising active carbon stocks in smallholder systems may be a strategic priority in many areas for incentivizing greater use of inorganic fertilizer, reversing land degradation, and achieving sustainable agricultural intensification.